Looking Back From the Future: Perspective Taking in Virtual Reality Increases Future Self-Continuity - Ganschow, Benjamin; Cornet, Liza; Zebel, Sven; van Gelder, Jean-Louis (Frontiers in Psychology, 2021)
In the current study, we tested a novel perspective-taking exercise aimed at increasing the connection participants felt towards their future self, i.e., future self-continuity. Participants role-played as their successful future self and answered questions about what it feels like to become their future and the path to get there. The exercise was also conducted in a virtual reality environment and in vivo to investigate the possible added value of the virtual environment with respect to improved focus, perspective-taking, and effectiveness for participants with less imagination. Results show that the perspective taking exercise in virtual reality substantially increased all four domains of future self-continuity, i.e., connectedness, similarity, vividness, and liking, while the in vivo equivalent increased only liking and vividness. Although connectedness and similarity were directionally, but not significantly different between the virtual and in vivo environments, neither the focus, perspective taking, or individual differences in imagination could explain this difference – which suggests a small, but non-significant, placebo effect of the virtual reality environment. However, lower baseline vividness in the in vivo group may explain this difference and suggests preliminary evidence for the dependency of connectedness and similarity domains upon baseline vividness. These findings show that the perspective taking exercise in a VR environment can reliably increase the future self-continuity domains.